COX-2/sEH Dual Inhibitor PTUPB Alleviates CCl4-Induced Liver Fibrosis and Portal Hypertension - Zhao, Zhifeng; Zhang, Chihao; Lin, Jiayun; Zheng, Lei; Li, Hongjie; Qi, Xiaoliang; Huo, Haizhong; Lou, Xiaolou; Hammock, Bruce D.; Hwang, Sung Hee; Bao, Yongyang; Luo, Meng (Frontiers in Medicine, 2021)
Background: PTUPB, a dual cyclooxygenase-2 (COX-2)/soluble epoxide hydrolase (sEH) inhibitor, was found to alleviate renal, pulmonary fibrosis and liver injury. However, little is known about the effect of PTUPB on liver cirrhosis. In this study, we aimed to explore the role of PTUPB in liver cirrhosis and portal hypertension (PHT). Method: Rat liver cirrhosis model was established via subcutaneous injection of carbon tetrachloride (CCl4) for 16 weeks. The experimental group received oral administration of PTUPB (10 mg/kg) for 4 weeks. We subsequently analyzed portal pressure (PP), liver fibrosis, inflammation, angiogenesis, and intra-/extrahepatic vascular remodeling. Additionally, network pharmacology was used to investigate the possible mechanisms of PTUPB in live fibrosis. Results: CCl₄ exposure induced liver fibrosis, inflammation, angiogenesis, vascular remodeling and PHT, and PTUPB alleviated these changes. PTUPB decreased PP from 17.50±4.65 to 6.37±1.40 mmHg, reduced collagen deposition and pro-fibrotic factor. PTUPB alleviated the inflammation and bile duct proliferation, as indicated by decrease in serum interleukin 6 (IL-6), liver Cytokeratin 19 (CK-19), transaminase and macrophage infiltration. PTUPB also restored vessel wall thickness of superior mesenteric arteries (SMA) and inhibited intra-/extrahepatic angiogenesis and vascular remodeling via vascular endothelial growth factor (VEGF), von Willebrand factor (vWF), etc. Moreover, PTUPB induced sinusoidal vasodilation by upregulating endothelial nitric oxide synthase (eNOS) and GTP-cyclohydrolase 1 (GCH1). In enrichment analysis, PTUPB engaged in multiple biological functions related to cirrhosis, including blood pressure, tissue remodeling, immunological inflammation, macrophage activation, and fibroblast proliferation. Additionally, PTUPB suppressed hepatic expression of sEH, COX-2, and transforming growth factor-β (TGF-β). Conclusion: PTUPB ameliorated liver fibrosis and PHT by inhibiting fibrotic deposition, inflammation, angiogenesis, sinusoidal and SMA remodeling. The molecular mechanism may be mediated via the downregulation of the sEH/COX-2/TGF-β.